Profil Penguasaan Keterampilan Proses Sains Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar - Prima Mutia Sari (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2018)
This study aimed to reveal science process skills profile of pre-service elementary school teacher in one of private universities in Jakarta students. The research method was descriptive. Research population was all students of pre-service elementary school teachers The sample was 5th semester students of year 2016/2017 as many as 316 students selected by Purposive Sampling technique. The research instruments were science skill test and science process skill observation sheet. Data analysis using descriptive statistics that included percentages, minimum values, maximum values, averages and standard deviations. The result showed that the proficiency of science skill process of pre-service elementary school teacher was still low with the average score of 46,46, the highest indicator was the ability to use the tools and the material and the lowest indicator was the ability to communicate